WTO AND UZBEKISTAN: BALANCE OF OPPORTUNITIES AND CHALLENGES FOR THE NATIONAL ECONOMY - Abdiualieva Gulzada Azatovna (European Science Publishing, 2024)
The article explores the process and prospects for Uzbekistan's accession to the World Trade Organization (WTO). The goals and principles of the WTO have been analyzed, as well as the experience of Kyrgyzstan as one of the first post-Soviet countries to join the organization. Particular attention is paid to the strategic opportunities and challenges that Uzbekistan faces in the process of integration into the global trading system.
Keywords: World Trade Organization (WTO), economic integration, trade liberalization, regulatory reforms, customs tariffs, international competition, economic development, globalization.